Aggressive driving behaviour – A review of the literature - Mohd Kassim, Muhammad Asyraf; Abdul Hanan, Suhaila; Aziz, Ahmad Bashir (School of Technology Management & Logistics (STML), 2019)
Road accidents in Malaysia keep increasing every year and most of the accidents ended with deaths, serious injuries and total loss of the vehicles. National Highway Safety Traffic Administration (NHSTA) (2017) defined road accidents as an event that occurs on a road open to public traffic; resulting in one or more persons being injured or killed, where at least one moving vehicle is involved. The phenomena of road accidents have been haunting the public as it can cause permanent disability and post-traumatic stress disorder to the drivers. Malaysia had experienced huge numbers of registered motor vehicles from 22,702,221 in 2013 to 26,904,539 in 2017. It shows about 15.62% growth for the last five years. Remarkably, in year 2017, the total number of motor vehicles in Malaysia is almost equal to the total population in that year. Increasing volume of motor vehicles will cause increasing number of interactions between road users’ and road accidents risk is getting higher (Ibrahim, Ismail, Halim & Amit, 2016)